Comparative evaluation of quality management practices in the public and private hospitals in Visakhapatnam District: An original research - Rahul V C. Tiwari; Sandesh K Sharma; Sujit R Sahoo; Srujan K Velthuru; Jeevan Matada Basavarajaiah; Madiha Kazi; Heena Dixit (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: In the Visakhapatnam District, this study compares the quality management procedures used by public and private hospitals. Knowing how these practices are similar and different from one another can help inform policy decisions and improve the quality of health care. Materials and Methods: A cross-sectional study design was used, and 100 hospitals from both public (50 hospitals) and private (50 hospitals) were included in the sample size. A standardized questionnaire that evaluated different aspects of quality management practices was used to gather the data. Descriptive statistics and inferential tests were used in the quantitative analysis. Results: Significant variations in quality management procedures between public and private hospitals were found. In terms of patient happiness, service responsiveness, and technological use, private hospitals scored better. Regarding accessibility, cost, and equity of healthcare services, public hospitals fared better. Conclusion: The report emphasizes the necessity of focused initiatives to improve quality management procedures in both public and commercial institutions. Collaboration between the two sectors can make it easier to deploy evidence-based tactics and share best practices to raise overall healthcare quality in the Visakhapatnam area.